2020
DOI: 10.3390/molecules25215052
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomotropic Features and Autophagy Modulators among Medical Drugs: Evaluation of Their Role in Pathologies

Abstract: The concept of lysosomotropic agents significantly changed numerous aspects of cellular biochemistry, biochemical pharmacology, and clinical medicine. In the present review, we focused on numerous low-molecular and high-molecular lipophilic basic compounds and on the role of lipophagy and autophagy in experimental and clinical medicine. Attention was primarily focused on the most promising agents acting as autophagy inducers, which offer a new window for treatment and/or prophylaxis of various diseases, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 131 publications
0
5
0
Order By: Relevance
“…Aberrant autophagy plays a key role in aging, type 2 diabetes mellitus, and neurodegeneration [34]. Suppression of autophagy in db/db mice partially resembles the changes that occur in aging [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aberrant autophagy plays a key role in aging, type 2 diabetes mellitus, and neurodegeneration [34]. Suppression of autophagy in db/db mice partially resembles the changes that occur in aging [35].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium-glucose cotransporter 2 (SGLT2) inhibitor empagliflozin and dipeptidyl peptidase 4 (DPP4) inhibitor linagliptin reactivate glomerular autophagy in db/db mice, thus manifesting a positive effect [37]. Recently, trehalose, an inducer of autophagy, was suggested as a possible positive factor in the control of neurodegeneration development and in the regulation of blood glucose levels [34,37]. Trehalose might also be used in the treatment of other diseases, such as cardiometabolic, liver, and other illnesses followed by disturbances in glucose metabolism [2,34,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that the underlying mechanism of the attenuated T-DM1 cytotoxicity involves primarily the lysosomal accumulation of drugs and the subsequent inhibition of SLC46A3 function. Macrolides are weakly basic amphiphiles that accumulate in lysosomes by ion trapping under acidic conditions. , Because SLC46A3 is a lysosomal transporter involved in the escape of Lys-SMCC-DM1 to the cytoplasm and is a critical determinant of T-DM1 therapeutic efficacy in vitro and in vivo, ,, the lysosomal accumulation of compounds that inhibit SLC46A3 may interfere with T-DM1 efficacy. Our previous work showed that lysosomotropic drugs that inhibit SLC46A3, including clarithromycin and erythromycin, reduce T-DM1 efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…Some compounds (β-glucans) have been proven to reduce risk factors of cardiovascular events, thereby improving the treatment of diabetes and of its complications [ 65 ]. Recently, trehalose, a known inducer of autophagy [ 10 , 66 , 67 ], was suggested as a possible therapeutic agent for the control of neurodegeneration and for the regulation of blood glucose levels. Trehalose treatment has significantly attenuated pathological changes in the hypothalamus (by inducing autophagy in this brain region) of mice and alleviated behavioral aberrations of mice in models of neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%